DISRUPSI DARI ATAS: KASUS BANGKRUTNYA KIOS TRADISIONAL BERHADAPAN DENGAN MINIMARKET MODERN - stefanus - rahoyo (Universitas Semarang, 2020)
Various studies have concluded that the presence of modern minimarkets has a negative impact on traditional kiosks. One of the negative impacts is revenue’s decrase of the tradisional kiosks. However, the various studies have not answered why and how the kiosts’ revenue decrase or even they bankrupted. Losing in competition is not a correct reason to explain the above phenomenon because the fact is—and is perceived so by consumers—the price of goods in traditional kiosks is cheaper than the price of the same goods in modern minimarkets.With a qualitative approach this study found that the phenomenon of revenue’s decrease and even the bankruptcy of traditional kiosks were because of disruption and not because they could not compete with modern minimarkets. It is, however, differ from Chistensen's disruptive innovation theory where disruption always starts from low-end market; this research found the opposite direction, namely disruption starting from high-end market or disruption from above.